2021
DOI: 10.17582/journal.sja/2021/37.3.735.741
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Maize Genotypes for Yield and Yield Attributes in Chitwan, Nepal

Abstract: M aize (Zea mays L.) is an important cereal crop after wheat and rice in the world (Khan et al., 2019). It belongs to Poaceae family. The word maize was originated from Spanish word 'Maiz' and it is domesticated variant of teosinte (Zea mexicana). Maize was domesticated first by natives of Mesoamerica. In Mexico, more diversity of maize has been reported (Khan et al., 2019). In 2018, maize had 1147.62 million tons production all over the world and in Asian region it had 361.56 million tons production. Asian re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
(14 reference statements)
2
0
0
Order By: Relevance
“…A lower average relative yield increase (4.03%) was recorded from a shift of 200 to 300 kg•ha −1 multinutrient fertilizer application level, indicating that the application of the multinutrient fertilizer beyond 200 kg•ha −1 is not expected to cause signifcant effects on maize yield. A similar efect of nutrient application levels on maize yield and its components was reported by [6,8,[50][51][52][53].…”
Section: Relative Change In Yield Caused By a Change In Sowingsupporting
confidence: 79%
“…A lower average relative yield increase (4.03%) was recorded from a shift of 200 to 300 kg•ha −1 multinutrient fertilizer application level, indicating that the application of the multinutrient fertilizer beyond 200 kg•ha −1 is not expected to cause signifcant effects on maize yield. A similar efect of nutrient application levels on maize yield and its components was reported by [6,8,[50][51][52][53].…”
Section: Relative Change In Yield Caused By a Change In Sowingsupporting
confidence: 79%
“…This result was similar with Neupane, B., Paudel, A., &Wagle P. (2020) who reported that signi cant variation is observed in number of leaves due to hybrid maize variety. Similar result was obtained in(Devkota, 2020) and (Neupane, B., Paudel, A., &Wagle P. 2020) Bastola, et al, (2021). also observed the signi cant divergences among deferent genotypes of maize in number of leaf per plant.…”
supporting
confidence: 82%